Unwoke : how to defeat cultural Marxism in America - Cruz, Ted, 1970- (Regnery Publishing, 2023)
"The Democratic Party is now controlled by Cultural Marxists. So are our universities and public schools, the media, Big Tech, and Big Business. Corporations push transgenderism down their customers' throats. Banks punish gun shops. Hollywood insults our religious beliefs and grooms our children. The big investment companies use our retirement savings to promote leftist causes. And the Biden administration has turned our military into an indoctrination camp, neglected transportation safety to focus on climate change, and persecuted peaceful pro-lifers while leaving prochoice arsonists at large"--